Is vaginal misoprostol more effective than oral misoprostol for cervical ripening in obese women?. (17th October 2020) - Soni, Shelly; Pappas, Karalyn; Lesser, Martin L.; Blitz, Matthew J.; Augustine, Stephanie A.; Rochelson, Burton
Abstract: Objective: To determine if vaginal misoprostol is more effective than oral misoprostol for cervical ripening in obese women. Study design: A retrospective cohort study of obese women undergoing induction of labor from Jan 2013 to Dec 2016 with singleton, viable pregnancies beyond 37 completed weeks of gestational age. Women with an initial Bishop score of 7 or less, with a cervical dilatation of less than 2 cm, who received either vaginal or oral misoprostol as a cervical ripening agent, were included. Primary outcome was interval from the start of induction to the attainment of 3 cm cervical dilatation. Secondary outcomes included the interval from the start of induction to delivery and the rate of cesarean delivery (CD). Result: Of women who met the inclusion criteria, 966 (75.5%) women received oral misoprostol and 314 (24.5%) received vaginal misoprostol. The mean time-interval from the start of induction to attainment of 3-cm dilatation was shorter in the vaginal group (10.5 ± 10.4 h) compared to the oral group (17.2 ± 11.5 h), ( p  < .0001). Significantly shorter times to delivery were also noted in the vaginal group (17.4 h for vaginal vs. 24.8 h for oral, p  < .0001). In the subgroup analysis of nulliparous women, shorter time intervals from the start of induction to attainment of 3-cm dilatation, as well as to delivery, were noted in the vaginal misoprostol group ( p  < .0001 for both). Multiple linear regression model confirmed route of misoprostol administration as an independent variable in predicting the outcomes (time from start of induction to 3 cm as well as to delivery). Significant findings amongst neonatal outcomes included lower umbilical artery pH and higher rates of neonatal jaundice in the oral misoprostol group. Conclusion: In a population of obese women undergoing induction of labor, vaginal administration of misoprostol was associated shorter time intervals from the start of induction to the attainment of 3 cm of dilatation, as well as to delivery, without increasing the rate of cesarean deliveries or the incidence of adverse maternal and neonatal outcomes.